Homeostatic Imbalance and Colon Cancer: The Dynamic Epigenetic Interplay of Inflammation, Environmental Toxins, and Chemopreventive Plant Compounds - Sokolosky, Melissa L.; Wargovich, Michael J. (Frontiers in Oncology, 2012)
The advent of modern medicine has allowed for significant advances within the fields of emergency care, surgery, and infectious disease control. Health threats that were historically responsible for immeasurable tolls on human life are now all but eradicated within certain populations, specifically those that enjoy higher degrees of socio-economic status and access to healthcare. However, modernization and its resulting lifestyle trends have ushered in a new era of chronic illness; one in which an unprecedented number of people are estimated to contract cancer and other inflammatory diseases. Here, we explore the idea that homeostasis has been redefined within just a few generations, and that diseases such as colorectal cancer are the result of fluctuating physiological and molecular imbalances. Phytochemical-deprived, pro-inflammatory diets combined with low-dose exposures to environmental toxins, including bisphenol-A (BPA) and other endocrine disruptors, are now linked to increasing incidences of cancer in westernized societies and developing countries. There is recent evidence that disease determinants are likely set in utero and further perpetuated into adulthood dependent upon the innate and environmentally-acquired genetic profile unique to each individual. In order to address a disease as multi-factorial, case-specific, and remarkably adaptive as cancer, research must focus on its root causes in order to elucidate the molecular mechanisms by which they can be prevented or counteracted via plant-derived compounds like epigallocatechin-3-gallate (EGCG) and resveratrol. The significant role of epigenetics in the regulation of these complex processes is emphasized here to form a comprehensive view of the dynamic interactions that influence modern-day carcinogenesis, and how restoring homeostatic balance may be the key to the cancer riddle.